Robusta Extract Cream Ameliorated Ultraviolet B-induced Wrinkle Skin of Mice by the Regulation of Epidermal Thickness and Inhibition of MMP-1 - Dimpuulina Erna Mariati; Sunarjati Sudigdoadi; Ronny Lesmana; Astrid Feinisa Khairani; Julia Windi Gunadi; Vita Murniati Tarawan; Unang Supratman; Hanna Goenawan (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Recently, coffee is widely used for preventing photoaging because of its antioxidant capacity. Among two kinds of coffee, robusta coffee has higher content of antioxidant such as chlorogenic acid (CGA) and caffeine. Researchs about robusta coffee bean effect on photoaging due to UVB radiation is still limited. Therefore, the aim of this study was to examine the effect of robusta extract cream (RE cream) on preventing wrinkle in mice induced by ultraviolet-B (UVB) radiation.METHODS: RE cream was made by mixing RE coffee with moisturizing cream in different concentration (10%, 20%, and 40%). Twenty-five male of Mus musculus Balb/c strain mice aged 4 weeks were divided into five groups; control group, UVB group, UVB + 10% RE group, UVB + 20% RE group, and UVB + 40% RE group. The UVB groups were given UVB radiation three times a week with an exposure duration of 100 seconds per time for ten weeks. At the end of the treatment, skin samples were excised and statined histologically, also were analyzed for their protein expression. Evaluation of wrinkles was carried out using the Bissete method before and after treatment. To evaluate the thickness of the epidermis, HE staining was performed, while masson Trichome staining was performed to determine the collagen content.RESULTS: RE cream-treated groups showed lower wrinkle score compared to the control group. Furthermore, in UVB + 10% RE group, the RE cream application reduce wrinkle formation. In UVB + 10% RE group and UVB + 20% RE group, the RE cream application increased epidermal thickness and collagen content (p=0.00). While collagenase, matrix metalloproteinase-1 (MMP-1) expression was lower in UVB + 20% RE group compared to the UVB group (p<0.05), however the MMP1 expression in UVB + 40% RE group was higher than other treatment group.CONCLUSION: RE cream prevents wrinkle by maintaining epidermal thickness and collagen contain. RE cream also decreases MMP-1 expression in mice.KEYWORDS: coffee, collagen, MMP-1, robusta, wrinkle